Reimagining “Beauty”: Young Adult Fairytale Retellings in Perpetuation of & Resistance to Patriarchy - Zoe Marriott (Leaf Journal)
In recent years, Young Adult (YA) fiction has – following its speculative adult counterparts – seen an influx of feminist dystopias. With this increase, comes a vast assortment of patriarchal systems created to coerce and control young female protagonists. What are the steps for YA writers wishing to create such high-concept patriarchies? Prior to writing is understanding that real-world patriarchies are social systems with interconnected power discourses. Social ideals are created and upheld by institutions such as education, science and religion, to create common norms – or ‘Group Think’ – ensuring women are ruled by men, whether it be actively or passively. Thus, when planning, writers must first form the feminist message their novel revolves around, before turning this idea directly on its head: the world in their novel should present the direct opposite of their message. Now, with the foundations of a patriarchy conceptualised, writers must focus on developing and maintaining the social norms which are to keep their protagonist oppressed and unhappy. Finally, to deliver the desired message, writers must plot to send their oppressed and unhappy protagonist on a journey through the patriarchy; it is up to the writer whether they come out the other side.